The environmental education with a transdisciplinary perspective in the context of the Brazilian legislation (Research, Society and Development, 2018)
The Brazilian legislation deals with the implication of a country in relation to Environmental Education, as an essential and permanent component of national education, and must be present at all levels and forms of educational process, both formal and non-formal. It should not be portrayed as a discipline, but an integrated educational practice that should be used as a whole. The present study is presented in an interdisciplinary and environmental way as a transdisciplinary perspective with the Environmental Management Systems, considering the context of the Brazilian legislation. Emphasis is placed on the importance of environmental management issues, transdisciplinarity with auxiliary assistance, as well as a working environment for environmental awareness. The work was developed through bibliographical research, with the purpose of obtaining information on Environmental Education. You may be able to evaluate the ability to behave as an efficient and environmental control tool whenever it works with concepts, values and behaviors as a whole, while at the same time other control instruments can contribute to the construction of a society with priority and balance of the whole environment.